Hsa_circ_0059511 promote glioma cell proliferation and migration through hsa-miR-194-5p/HBEGF axis - Yajun Jing; Huang-cheng Shang-guan; Jiawei Cai; Jinye Su; Wei Huang; Qiu He; Xiaoyong Chen; Dezhi Kang; Zanyi Wu (Cancer Cell International)
Abstract A growing number of studies have highlighted the critical role that circular RNAs play in cancer. We previously observed that hsa_circ_0059511 was markedly upregulated in glioma tissues, suggesting that it may play an oncogenic role in gliomas. But its mechanism is not clear. The aim of the present study was to investigate the biological function of hsa_circ_0059511 in gliomas. First, the expression levels of heparin-binding EGF-like growth factor (HBEGF), hsa_circ_0059511, and hsa-miR-194-5p in glioma tissues and cells were measured by qRT-PCR. Furthermore, cell viability, migration, and invasion were evaluated in vitro using CCK8 assay, EdU assay, and Transwell invasion assay after pcNDA-hsa_circ_0059511 transfection to increase hsa_circ_0059511 and siRNA transfection to suppress hsa_circ_0059511 in glioma cells. Finally, RNA immunoprecipitation (RIP) and a dual-luciferase reporter assay were used to determine the association between hsa-miR-194-5p and hsa_circ_0059511 or HBEGF. Our results showed that the expression levels of hsa_circ_0059511 were significantly increased in glioma tissues and cells compared to the control group (all p < 0.05). Furthermore, cell proliferation and invasion in vitro were restricted by knockdown of hsa_circ_0059511. Of note, we found that downregulation of hsa-miR-194-5p, a target microRNA of hsa_circ_0059511, could reverse the reduction in glioma cell proliferation and migration caused by silencing of hsa_circ_0059511. At the same time, we also found that hsa-miR-194-5p could suppress the proliferation and migration of glioma cells by inhibiting the expression of HBEGF, a target gene of hsa-miR-194-5p. Overall, our results showed that hsa_circ_0059511 increased HBEGF expression by sponging hsa-miR-194-5p to promote tumor cell migration and proliferation.